Vehicular Multilevel Data Arrangement-Based Intrusion Detection System for In-Vehicle CAN. (20th January 2022) - Kim, Wansoo; Lee, Jungho; Lee, Yousik; Kim, Yoenjin; Chung, Jingyun; Woo, Samuel
Abstract : Modern vehicles are equipped with various types of electrical/electronic (E/E) systems. Electronic control units (ECUs) are used to control various E/E systems in the vehicle. For efficient information exchange between ECUs, most vehicle manufacturers use the Controller Area Network (CAN) protocol. However, CAN has security vulnerabilities because it does not have an authentication or encryption method. Since attacks on in-vehicle networks affect the safety of drivers, it is essential to develop a technology to prevent attacks. The intrusion detection system (IDS) is one of the best ways to enhance network security. Unlike the traditional IDS for network security, IDS for the in-vehicle network requires a lightweight algorithm because of the limitation of the computing power of in-vehicle ECUs. In this paper, we propose a lightweight IDS algorithm for in-vehicle CAN based on the degree of change between successive data frames. In particular, the proposed method minimizes the load on the ECU by using the CAN data frame compression algorithm based on exclusive-OR operations as a tool for calculating the degree of change.